2016
DOI: 10.1155/2016/2829583
|View full text |Cite
|
Sign up to set email alerts
|

Current Diagnostic and Therapeutic Aspects of Eosinophilic Myocarditis

Abstract: Eosinophilic myocarditis (EM) represents a rare form of myocardial inflammation with very heterogeneous aetiology. In developed countries, the most prevalent causes of EM are hypersensitivity or allergic reactions, as well as hematological diseases leading to eosinophilia. The disease may have a variable clinical presentation, ranging from asymptomatic forms to life-threatening conditions. Most patients with EM have marked eosinophilia in peripheral blood. Endomyocardial biopsy needs to be performed in most ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
141
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(146 citation statements)
references
References 25 publications
1
141
1
3
Order By: Relevance
“…The most important cationic proteins are major basic protein, eosinophilic cationic protein, eosinophil-derived neurotoxin and eosinophilic peroxidase. These proteins can induce cellular apoptosis and necrosis when degranulation of eosinophils occurs 7. Eosinophils acquire IL-5 receptor α on their surface at the early stage during eosinophilopoiesis, differentiation and maturation, mainly under the influence of IL-5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important cationic proteins are major basic protein, eosinophilic cationic protein, eosinophil-derived neurotoxin and eosinophilic peroxidase. These proteins can induce cellular apoptosis and necrosis when degranulation of eosinophils occurs 7. Eosinophils acquire IL-5 receptor α on their surface at the early stage during eosinophilopoiesis, differentiation and maturation, mainly under the influence of IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CCR3 expressed in eosinophils will accumulate in cardiomyocytes, which leads to damage of heart tissue. Recent literature has indicated that eosinophilic infiltration and degranulation are associated with myocardial necrosis 7. Moreover, eosinophils bind to thrombomodulin, causing impaired formation of the thrombomodulin–thrombin complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis pathogenesis and treatment of the eosinophilic myocarditis was reviewed recently by Kuchynka et al, (12*). Although often associated with hypersensitivity responses to drugs and other allergens, many cases follow a viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…The nonspecific signs are cardiac chest pain, dyspnea, fatigue, palpitations and syncope. Furthermore, allergic manifestation such as fever, rashes and blood eosinophilia may occur 5 . However, symptoms and signs of hypersensitivity are not present in all patients 6 .…”
mentioning
confidence: 99%